2009
DOI: 10.1007/s10926-009-9223-y
|View full text |Cite
|
Sign up to set email alerts
|

Vocational Interventions for Unemployed: Effects on Work Participation and Mental Distress. A Systematic Review

Abstract: Based on our review, we conclude that there is weak evidence to support the use of vocational interventions to improve work participation and limited evidence to reduce mental distress for the unemployed. We recommend further development and evaluation of return to work intervention strategies for unemployed individuals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
83
1
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 105 publications
(86 citation statements)
references
References 22 publications
1
83
1
1
Order By: Relevance
“…A systematic review from 2010 concluded that the evidence supporting the use of vocational interventions to improve re-employment and reduce mental distress were weak 40. However, evidence from the USA41 and Finland42 indicate that psychological interventions targeting the unemployed effectively improved mental health, and were positively associated with re-employment.…”
Section: Discussionmentioning
confidence: 99%
“…A systematic review from 2010 concluded that the evidence supporting the use of vocational interventions to improve re-employment and reduce mental distress were weak 40. However, evidence from the USA41 and Finland42 indicate that psychological interventions targeting the unemployed effectively improved mental health, and were positively associated with re-employment.…”
Section: Discussionmentioning
confidence: 99%
“…Up to now, little attention has been paid to the development and evaluation of RTW interventions for sicklisted workers without an employment contract, such as temporary agency workers, those with an expired fixed-term contract, and unemployed workers (15). This is an important concern as these workers seem to have a more vulnerable position in the labor market.…”
mentioning
confidence: 99%
“…In Western societies, it is generally difficult to ‘survive’ as unemployed without participating in measures that range from short courses aimed at promoting job seeking skills, to long-term occupational training with integrated periods of work and to state subsidised job creation schemes. Studies concerning ‘indirect employment effects’ of the ALMP measures, or the health effects of ‘interrupted unemployment’, are excluded from the review of van der Noordt et al 1 The current body of such research is scarce,9 10 and rather than allowing unequivocal conclusions, the evidence gives some reason to recommend carefully designed prospective studies that make use of the natural experiments provided by various ALMP measures.…”
mentioning
confidence: 99%